14.0k views
2 votes
hello I'd like to know what
7 {x}^(2) - 5x + 3minus
(2 {x}^(2) + 7x - 4)equals to

User Criz
by
5.1k points

1 Answer

4 votes

7x^2-5x+3\text{ minus }(2x^2+7x-4)\text{ can be translated algebraically as}
7x^2-5x+3-(2x^2+7x-4)

Distribute the negative to the second trinomial and simplify by adding like terms. We get the following:


\begin{gathered} 7x^(2)-5x+3-(2x^(2)+7x-4) \\ =7x^2-5x+3-2x^2-7x+4 \\ =7x^2-2x^2-5x-7x+3+4 \\ =5x^2-12x+7 \\ \\ \text{Therefore,} \\ 7x^2-5x+3-(2x^2+7x-4)=5x^2-12x+7 \end{gathered}

User Charles Chow
by
5.7k points